Challenges of Geography in Nepal - Awasthi, Tara Prasad (The Third Pole: Journal of Geography Education, 2019)
Geography is the science of place and space. It focuses on mechanism of people, place and environment in general and people and their activities in particular. This paper attempts to analyze challenges of geography education in Nepal. For this, data were collected from both the primary and secondary sources through interviews, group discussion and field observation covering five schools and campuses offering geography. Knowledge of geography is necessary for each and every citizen for the national development. It requires effective geography education at various levels that introduces national territory, topography, soil, water, climate, vegetation, people, settlement, planning and resources. However, the geography education has been taught as an optional subject and it is competing with the other subjects like computer science, optional math, and economics in secondary and higher secondary levels in Nepal. As a result, there is no room for choosing geography as an optional subject to majority of students. They forced to select their least favored subject which was decided by school. Nowadays, the number of schools and students have been decreasing in geography subject at both school and university level.